2016
DOI: 10.1111/iju.13189
|View full text |Cite
|
Sign up to set email alerts
|

Safety of fondaparinux for prevention of postoperative venous thromboembolism in urological malignancy: A prospective randomized clinical trial

Abstract: Fondaparinux is non-inferior to low molecular weight heparin with respect to risk of bleeding. The favorable safety profile of fondparinux supports its prophylactic use as an alternative to low molecular weight heparin after surgery for urological malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…These changes can lead to several postoperative complications, such as VTE and bleeding. It has been reported that VTE and bleeding at or greater than CD grade III after curative resection of primary colorectal cancer occurs at rates of 0 to 0.16% and 0.2 to 0.81%, respectively [22][23][24]. Compared with these data, in the present study, VTE and bleeding events more frequently occurred (Table 4).…”
Section: Discussioncontrasting
confidence: 44%
“…These changes can lead to several postoperative complications, such as VTE and bleeding. It has been reported that VTE and bleeding at or greater than CD grade III after curative resection of primary colorectal cancer occurs at rates of 0 to 0.16% and 0.2 to 0.81%, respectively [22][23][24]. Compared with these data, in the present study, VTE and bleeding events more frequently occurred (Table 4).…”
Section: Discussioncontrasting
confidence: 44%
“…Moreover, there was no significant difference in the incidence of postoperative bleeding or other adverse events between the two groups. The results suggested that fondaparinux had good safety, supporting its prophylactic use after surgery for urinary malignancies ( Hata et al, 2016 ).…”
Section: Resultsmentioning
confidence: 92%
“…While for several years the standard therapy of LMWH has been in use, the trend has been changing towards factor Xa inhibitors (fondaparinux) because of their selectivity in action [9]. Fondaparinux was the first approved drug among factor Xa inhibitors [10] and is a synthetic pentasaccharide that selectively binds to antithrombin, making it rapidly inhibit factor Xa, a key enzyme in the coagulation pathway [9][10][11][12][13][14][15][16][17][18]. Pharmacokinetic analysis suggested that fondaparinux has rapid and complete absorption and a longer half-life, resulting in 24-h coverage without crossreacting with heparin-induced antibodies, and no need for monitoring of platelet counts [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Several trials have shown the benefit-risk ratio of fondaparinux over enoxaparin in preventing VTE in various patient profiles. Much of the evidence was either generated from randomized or specific cohort studies, under controlled clinical conditions [4,6,[12][13][14][15]18]. Hence, it is important to re-evaluate the performance of fondaparinux under uncontrolled clinical conditions such as real-world settings.…”
Section: Introductionmentioning
confidence: 99%